2018
DOI: 10.1097/aud.0000000000000524
|View full text |Cite
|
Sign up to set email alerts
|

Digit Triplet Test Hearing Screening With Broadband and Low-Pass Filtered Noise in a Middle-Aged Population

Abstract: The Flemish DTT with broadband noise had high sensitivity and specificity to detect high-frequency hearing impairment in middle age. Similar results were obtained for low-pass filtered noise when cutoff values for referral were age adjusted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 15 publications
3
13
4
Order By: Relevance
“…For the DTT, the reference value of−11.1 (±1.6) dB SNR obtained in this study agrees with previously reported values of−11.5 and−11.1 dB SNR for young (20–30 years) and middle-aged (40–60 years) adults (Vercammen et al., 2017), respectively, and the original reference value of −11.7 dB SNR found by Jansen et al. (2013) in young adults.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…For the DTT, the reference value of−11.1 (±1.6) dB SNR obtained in this study agrees with previously reported values of−11.5 and−11.1 dB SNR for young (20–30 years) and middle-aged (40–60 years) adults (Vercammen et al., 2017), respectively, and the original reference value of −11.7 dB SNR found by Jansen et al. (2013) in young adults.…”
Section: Resultssupporting
confidence: 92%
“…A growing trend has been the use of automated suprathreshold self-tests based on speech perception in noise for adult hearing screening (De Sousa, Swanepoel, Moore, & Smits, 2018; Folmer, Vachhani, Mcmillan, Kidd, & Feeney, 2017; Jansen et al., 2010; Jansen, Luts, Dejonckere, van Wieringen, & Wouters, 2014; Koole et al., 2016; Potgieter, Swanepoel, Myburgh, & Smits, 2018a; Smits & Houtgast, 2005; Smits, Merkus, & Houtgast, 2006; Vercammen, Goossens, Wouters, & van Wieringen, 2017; Vlaming, MacKinnon, Jansen, & Moore, 2014; Watson, Kidd, Miller, Smits, & Humes, 2012), for example, for online hearing screening and screening via mobile devices (Stenfelt, Janssen, Schirkonyer, & Grandori, 2011). One commonly used test is the Digit Triplet Test (DTT), in which combinations of three digits are presented in speech-shaped noise at different signal-to-noise ratios (SNRs) using an adaptive test procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Using a fixed-SNR procedure, Smits (2017) showed that the number of digit triplets in a DIN could be reduced to as few as 8 trials, without compromising sensitivity and specificity but sacrificing accurate estimation of the SRT. Furthermore, with the early appearance and high prevalence of high frequency hearing loss, use of low-pass filtered masking noise to improve sensitivity of the DIN to high frequency hearing loss has been investigated, showing either higher (Vlaming et al 2014) or similar (Vercammen et al 2018) area under the receiver operating characteristics (ROC) curve compared to DINs with standard speech-shaped noise. Therefore, when using homogenized digits to ensure high testretest reliability, these modifications could make the DIN test more applicable to persons with noise-induced or age-related hearing loss (Vlaming et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated a high sensitivity (91%) as well as a high specificity (93%) [63]. A recent trial by Vercammen et al (2017) reported that a Flemish version of the digit triplet test, which was used with broadband noise, had a high sensitivity and high specificity to detect high-frequency hearing impairment in middle-aged persons [64]. Although SPIN tests are commonly used to assess patients’ speech intelligibility, there are only a few eHealth applications available that include SPIN tests.…”
Section: Screening Methods For Age-related Hearing Loss In Older Pmentioning
confidence: 99%